PERLINDUNGAN HUKUM TERHADAP PEMAIN SEPAK BOLA DI INDONESIA ATAS HAK POKOKNYA - Sihasale, Giovanni Gianini; Setyadji, Sri; Hufron (INSPIREE: Indonesian Sport Innovation Review, 2021)
The purpose of the study. Revealing the legal protection of football players as workers in the football "industry" and as a worker / laborer for a club, so that the Manpower Law can be applied. Materials and methods. This research uses a juridical-normative approach which is expected to provide more understanding to the players in the world of sports, especially in the field of football in Indonesia. Results. The fact is that soccer players, as workers or laborers, still have not got the rights they should receive, and also most of them still do not understand or do not really understand the contents of the contracts they have signed. Conclusions. A bright spot where PSSI as the parent of national football has made changes by forming the NDRC where its task is to resolve disputes between players and football clubs.